ANALISIS KOMPETENSI PEDAGOGIK GURU DALAM PEMBELAJARAN IPA TERPADU SMP KELAS IX SE KECAMATAN PAGARAN TAPAH DARUSSALAM KABUPATEN ROKAN HULU TAHUN PEMBELAJARAN 2014/2015 - Wahyuni, Sri; Afifah, Nurul; Brahmana, Eti Meirina (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The aims of this study was to know the ability of teachers in the implementation of learning pedagogical Integrated Science is Junior High Class IX se District of Pagaran Tapah Darussalam Rokan Hulu Learning Year 2014/2015. This research is a descriptive study. Samples taken from the entire population of 5 teacher. The sampling technique in this paper is saturated sample is a sampling technique when all the population is used as a sample. Result showed the ability of teacher in junior class IX District of Pagaran Tapah Darussalam Rokan Hulu is good perfomed with ability pedagogical value 81.86%